Mouth development. (17th May 2017) - Chen, Justin; Jacox, Laura A.; Saldanha, Francesca; Sive, Hazel
Abstract : A mouth is present in all animals, and comprises an opening from the outside into the oral cavity and the beginnings of the digestive tract to allow eating. This review focuses on the earliest steps in mouth formation. In the first half, we conclude that the mouth arose once during evolution. In all animals, the mouth forms from ectoderm and endoderm. A direct association of oral ectoderm and digestive endoderm is present even in triploblastic animals, and in chordates, this region is known as the extreme anterior domain (EAD). Further support for a single origin of the mouth is a conserved set of genes that form a 'mouth gene program' including foxA and otx2 . In the second half of this review, we discuss steps involved in vertebrate mouth formation, using the frog Xenopus as a model. The vertebrate mouth derives from oral ectoderm from the anterior neural ridge, pharyngeal endoderm and cranial neural crest (NC). Vertebrates form a mouth by breaking through the body covering in a precise sequence including specification of EAD ectoderm and endoderm as well as NC, formation of a 'pre‐mouth array, ' basement membrane dissolution, stomodeum formation, and buccopharyngeal membrane perforation. In Xenopus, the EAD is also a craniofacial organizer that guides NC, while reciprocally, the NC signals to the EAD to elicit its morphogenesis into a pre‐mouth array. Human mouth anomalies are prevalent and are affected by genetic and environmental factors, with understanding guided in part by use of animal models. WIREs Dev Biol 2017, 6:e275. doi: 10.1002/wdev.275 This article is categorized under: Early Embryonic Development > Development to the Basic Body Plan Birth Defects > Craniofacial and Nervous System Anomalies Comparative Development and Evolution > Body Plan Evolution Abstract : The mouth is essential for eating and has ancient origins. Comprising ectodermal and endodermal lineages, the mouth forms by a multistep process, whose disruption contributes to facial anomalies.